Healing with sound: Exploring possible applications of Qur’anic recitation in human cells - Hashim, Rosyafirah; Zainuddin, Zainul Ibrahim; Zulkifly, Ahmad Hafiz; Mohamad, Mohd Yusof; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa’zamuddin; Sha'ban, Munirah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Tissue engineering offers an alternative method to facilitate for in vitro cell-based regeneration of tissues/organs for in vivo implantation. Sound therapy has long been used in dealing with various health problems. Known to have certain effects on emotional reactions in the humans, the number of research done in relation to sound healing has grown consistently. It is believed that not only the brain or the auditory cells react to the sound, other cells of the human body also responded well to it. Perhaps, sound healing can also be used to address degenerative diseases in the humans. Degenerative diseases result from a continuous process based on degenerative cell changes, affecting tissues/organs, which will deteriorate over time. The changes may be due to physiological bodily wear or unfavourable lifestyle habits. In the Islamic tradition, the use of Qur’anic verses recitation for therapeutic purposes can be traced back to the times of Prophet Muhammad (صلى الله عليه وسلم .(Listening to the Qur’anic recitation is known to have therapeutic effects even on individuals who do not understand the meaning of the verses. Possibly, the melodious Qur’anic recitation could also function as sound therapy. However, there has been lack of literature suggesting systematic studies on the effect of Qur’anic verses recitation on human cells and their behavioral changes in vitro. Similar to the use of sound healing, Qur’anic recitation is also expected to have positive effect on the human body. As one of the healing mediums, Qur’anic recitation is hoped to have a more favourable effect than the conventional sound therapy. This paper aims to identify and briefly review any previous researches relevant to sound healing on human cells. It is hoped that this study could shed some light on the potential use of the Qur’anic recitation to facilitate for in vitro cell-based regeneration in tissue engineering studies.